DOES STRONG FACULTY SUPPORT EQUAL CONSISTENT COURSE COMPLETION? IT HAS FOR DALLAS BAPTIST UNIVERSITY - Shelton, Kaye (Online Learning, 2009)
Dallas Baptist University (DBU) is a private, Christian, liberal arts institution located in the DFW Metroplex. Just over 5,200 students, DBU provides both traditional undergraduate, adult and graduate degrees with the enrollment almost equally divided between the three student groups. Today, DBU offers 34 degree programs fully online maintain a course completion rate of 92–93% each semester with almost 2,000 students taking online classes. Because of its continued success and dedication to quality course development, the DBU online education department has become a model for several other higher education institutions.